2019
DOI: 10.1002/cpdd.644
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Randomized, Placebo‐Controlled Trial With a Topical Inhibitor of Stearoyl‐Coenzyme A Desaturase 1 Under Occluded and Nonoccluded Conditions

Abstract: Stearoyl‐coenzyme A desaturase 1 (SCD‐1) in sebaceous glands is a key enzyme in the synthesis of monounsaturated fatty acids essential for acne development. GSK1940029 gel, a novel SCD‐1 inhibitor, is being developed as a potential treatment for acne. To assess the irritation potential, pharmacokinetics (PK), and safety of topical GSK1940029 to the skin of healthy adults, two interdependent studies were conducted in parallel. Study 1 (n = 54) investigated the irritation potential of GSK1940029 (0.3% and 1%, oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Many of these compounds have nanomolar values of IC 50 . The inhibitor GSK1940029 has been in a phase I clinical trial as a topical treatment for acne and found to be well tolerated 177 . Intriguingly, SCD1 inhibition can alleviate α-synuclein cytotoxicity associated with Parkinson disease 178 , and clinical trials are being implemented.…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
“…Many of these compounds have nanomolar values of IC 50 . The inhibitor GSK1940029 has been in a phase I clinical trial as a topical treatment for acne and found to be well tolerated 177 . Intriguingly, SCD1 inhibition can alleviate α-synuclein cytotoxicity associated with Parkinson disease 178 , and clinical trials are being implemented.…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
“…55 SCD1 is a potential target in the treatment of acne. 56 Nonetheless, little information is available about the role of desaturation of FFAs in lipoinflammation in sebocytes. The observed lipogenic effects of C16:0 in SZ95 cells are to be considered, also supported by the EGF presence in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of SCD1 and FADS2 expression is associated with activation of inflammatory response in sebocytes 55 . SCD1 is a potential target in the treatment of acne 56 . Nonetheless, little information is available about the role of desaturation of FFAs in lipoinflammation in sebocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The elevated FAS in p53-inactivated cancer cells raises the hypothesis that these cells may be more sensitive to disruption of this process. Several SCD1 and FASN inhibitors are currently ongoing clinical trials (59,(68)(69)(70)(71), emphasizing the clinical importance of identifying biomarkers for drug sensitivity. We therefore analyzed the sensitivity to SCD1 inhibition across 26 human BC cell lines.…”
Section: P53 Inactivation-induced Fas Renders Cells Sensitive To Scd1...mentioning
confidence: 99%